Postgenomic aspects of resistance to acetylsalicylic acid in patients with coronary artery disease - Yu. I. Grinshtein; A. A. Kosinova; A. N. Maltseva; T. N. Subbotina; K. S. Semashchenko; P. I. Levagina; E. O. Shavrina; A. A. Savchenko (Российский кардиологический журнал, 2024)
Aim. To study the expression level of the P-selectin gene (SELP) mRNA and the level of intercellular interaction in patients with coronary artery disease (CAD) before and after coronary artery bypass grafting (CABG) in patients with resistance to acetylsalicylic acid (ASA).Material and methods. The study included 65 patients with CAD who were scheduled to CABG. SELP expression, the platelet-leucocyte aggregate level, and the level of P-selectin expression on aggregates were determined in all participants. Resistance to ASA was defined as platelet aggregation with arachidonic acid ≥20% in at least one sample. All studies were performed before and on the 8th-10th day after CABG.Results. Among patients, 29,4% (n=30) were resistant to ASA (ASA-R) at least at one point, while 7,8% (n=8) acquired resistance after CABG. ASA-R had a higher level of SELP (0,41 [0,28; 0,48] vs 0,32 [0,23; 0,39], p=0,037), absolute content of monocyte-platelet aggregates (24,70 [9,69; 39,90] vs 10,15 [5,27; 30,63], p=0,037) and relative amount of platelet-platelet CD62P aggregates (7,37% [3,43; 35,49] vs 4,84% [0,90; 9,63], p=0,045). A negative correlation was found between SELP expression and the relative content of monocyte-platelet aggregates (ρ=-0,349, p=0,013) on days 8-10 after CABG. Mmultivariate regression analysis found that the level of SELP gene mRNA expression is a predictor of ASA resistance before CABG (odds ratio 404,48; 95% confidence interval 1,68-97461,63).Conclusion. Increased SELP expression is associated with an increase in platelet aggregation activity, which contributes to an insufficient platelet response to antithrombotic therapy in patients with CABG. The level of SELP gene mRNA expression can be considered as a predictor of ASA resistance.